KONSEP PENDIDIKAN AGAMA ISLAM BERBASIS MULTIKULTURAL - Ubabuddi Ubabuddin (AT-TURATS, 2018)
Indonesia is a country rich in diversity. The diversity of religion, ethnicity, language, culture, and custom makes the country of Indonesia as a country different from other countries. This diversity must be accepted, acknowledged, and respected. This shows that the people of Indonesia is a multicultural society. To realize and support multiculturalism in Indonesia requires a sense of tolerance, mutual respect and mutual respect. The attitude of mutual respect and respect can be nurtured through multicultural education.